2014
DOI: 10.1515/polyeng-2014-0124
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of electrospun trans-polyisoprene nanofibers

Abstract: Abstract:The method of manufacturing nanofibers using the electrospinning technique from trans-polyisoprene (TPI) is presented in this study, possibly for the first time.The process parameters such as solution concentration, applied voltage, distance and feeding rate for electrospinning were investigated and optimized with respect to fiber morphology, as observed from scanning electron microscopy (SEM) photomicrographs. Smooth and uniform nanofibers were found to generate at the optimum conditions with 1% melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The EP‐1 and EP‐6 extract showed an endothermic peak in a temperature range from 50 to 65°C in cycles 1 and 3 (Figure 2). This temperature, according to Chen et al 28 corresponds to the fusion of the polyisoprenes and lipophilic compounds present in the extracts. This is because these authors analyzed trans ‐polyisoprenes and identified an endothermic peak in the temperature range from 40 to 60°C.…”
Section: Resultsmentioning
confidence: 99%
“…The EP‐1 and EP‐6 extract showed an endothermic peak in a temperature range from 50 to 65°C in cycles 1 and 3 (Figure 2). This temperature, according to Chen et al 28 corresponds to the fusion of the polyisoprenes and lipophilic compounds present in the extracts. This is because these authors analyzed trans ‐polyisoprenes and identified an endothermic peak in the temperature range from 40 to 60°C.…”
Section: Resultsmentioning
confidence: 99%
“…8 The nanofibers obtained from electrospinning have high specific surface area, aspect ratio, low surface roughness, and low porosity. 9,10 Electrospinning can also fabricate nano- and submicro-scale fibrous mats. This paper provides a comprehensive overview on polymer nanofibers and nanocomposite nanofibers.…”
Section: Introductionmentioning
confidence: 99%